Chronic effects of trichloroethylene upon S-100 protein content and lipid composition in gerbil cerebellum. - Kyrklund, T.; Goracci, G.; Haglid, Kenneth G.; Rosengren, L.; Porcellati, G.; Kjellstrand, P. (Scandinavian Journal of Work, Environment & Health, 1984)
Gerbil rats were exposed to trichloroethylene (TCE) vapors intermittently (8 h/d) at 510 ppm or continuously at 170 ppm for five months. The cerebellar content of S-100 protein and the phospholipid fatty-acid profiles were determined. S-100 protein, a possible marker for astrocytic reactivity, indicated delayed astrocytic reactivity in the anterior cerebellar hemisphere and a decrease of S-100 protein in the posterior cerebellar vermis. Minor lipid changes were observed. The fatty-acid profiles of ethanolamine phosphoglycerides showed a tendency towards alterations among the 22-carbon fatty acids, with a decrease in 22:5 (N-3), similar to those shown earlier for cerebral cortex and hippocampus of the gerbil. Two monoenoic fatty acids were decreased, the 20:1 of phosphatidyl-ethanolamine and the 18:1 of the phosphatidyl-serine. This occurrence could indicate a decrease in myelin in areas where these two fatty acids were found to be enriched.